1998
DOI: 10.1074/jbc.273.41.26361
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Retention of Recombinant GABABReceptors

Abstract: ␥-Aminobutyric acid type B (GABA B ) receptors mediate the transmission of slow and prolonged inhibitory signals in the central nervous system. Two splice variants of GABA B receptors, GABA B R1a and GABA B R1b, were recently cloned from a mouse cortical and cerebellar cDNA library. As predicted, these receptors belong to the G protein-coupled receptor superfamily. We have used epitope-tagged versions of GABA B R1a receptors to study the cellular distribution of these proteins in a variety of non-neuronal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(150 citation statements)
references
References 41 publications
9
137
0
4
Order By: Relevance
“…Indeed, the GABA B receptor can activate efficiently phospholipase C when co-expressed with the chimeric G-protein Gqi9 (47). As noticed previously, the IP assay is much more sensitive than the [␥- 35 S]GTP assay as indicated by the 100-fold lower EC 50 value measured for GABA compare with the [␥- 35 S]GTP assay. This probably results from the large amplification of the signaling cascade between G-protein activation and IP formation.…”
Section: Cgp7930 Is a Positive Allostericmentioning
confidence: 59%
See 1 more Smart Citation
“…Indeed, the GABA B receptor can activate efficiently phospholipase C when co-expressed with the chimeric G-protein Gqi9 (47). As noticed previously, the IP assay is much more sensitive than the [␥- 35 S]GTP assay as indicated by the 100-fold lower EC 50 value measured for GABA compare with the [␥- 35 S]GTP assay. This probably results from the large amplification of the signaling cascade between G-protein activation and IP formation.…”
Section: Cgp7930 Is a Positive Allostericmentioning
confidence: 59%
“…The dose-response curves were fitted using the Kaleidagraph program and the equation y ϭ [(y max Ϫ y min )/(1 ϩ (x/EC 50 ) nH )) ϩ y min , where the EC 50 is the concentration of the compound necessary to obtain 50% of the maximal effect and n H is the Hill coefficient. EC 50 for GABA was increased 3-and 10-fold in the presence of 0.1 and 1 mM CGP7930, respectively (42.0 Ϯ 11.0, 30.0 Ϯ 7.5, and 4.7 Ϯ 1.04 M in the absence or the presence of 0.1 and 1 mM CGP7930, respectively). A small increase in the binding of [␥- 35 S]GTP binding also was observed in the absence of GABA, suggesting that CGP7930 also may be able to slightly activate the receptor.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas GABA B agonists and competitive antagonists interact in the GABA B1 VFTM (Galvez et al, 1999;Galvez et al, 2000), this subunit expressed alone does not give rise to consistent responses. Although this subunit is retained in the ER due to a retention signal in its C-terminal tail (Couve et al, 1998;Pagano et al, 2001), no function can also be observed with a subunit mutated in the ER retention signal , whereas robust responses can be obtained in the presence of GABA B2 . Indeed, this second subunit, although unlikely to bind any ligand (Kniazeff et al, 2002), i) unmasks the ER retention signal of GABA B1 allowing the heterodimer to reach the cell surface ; ii) increases agonist affinity on GABA B1 (Kaupmann et al, 1998); C) plays a major role in G-protein coupling of the heteromer (Duthey et al, 2002).…”
Section: Class-c Gpcrs Are Dimers a Necessity For The Intramolecularmentioning
confidence: 99%
“…En revanche, la sous-unité GABA B2 est correctement exprimée à la surface, mais elle est en revanche incapable de lier le ligand et donc de déclencher l'activation des voies de signalisation intracellulaires. L'hétérodimérisation des deux sous-unités dans le RE masque le signal de rétention sur GABA B1 et favorise ainsi l'expression de l'hétérodimère à la surface cellulaire [26,27]. Une fois le dimère exprimé à la surface, GABA B1 peut lier le ligand et GABA B2 peut transduire l'effet du ligand en couplage avec les protéines G. La sous-unité GABA B2 possédant un domaine de liaison semblable à GABA B1, mais qui est incapable de lier le ligand, peut être considérée comme un récepteur orphelin à 7TM [28] (Figure 2).…”
Section: L'hétérodimérisation Des Rcpg Orphelins : Le Moyen De Commununclassified